Pengaruh Konsentrasi Aktivator Asam Klorida (HCl) Terhadap Kapasitas Adsorpsi Arang Aktif Kulit Buah Kakao (Theobroma cacao. L) Pada Zat Warna Methanil Yellow - Arung, Sitti; Yudi, Muh.; Chadijah, St (Al-Kimia, 2014)
Cocoa’s peel is a waste which usually burned, stacked or disintegrated and can make pollution to the environment. This condition motivates the researcher to produce the value-added product from the cocoa’s peel, such as activated carbon and as well as it can solve the environmental problems. This research aims to know the influence to use variation of concentration of activator HCl whice produces the optimum adsorption capacity from charcoal active of cocoa’s peel to the substance color of methanil yellow. Active carbon which is used in this research comes from cocoa’s peel which granular types with standard -100+40 mesh. Carbon is activated by physics in furnace with 600°C heat during 2 hours and is activated by chemistry with submerged of HCI 1M, 2M, 3M, 4M and 5M during 24 hours. The result of this research shows that optimum concentration in HCI 1M with adsorption capacity from charcoal active of cocoa’s peel is as large as 1,572 mg/g. Whereas knowing the influence of activator is used tabulation method by statistically, where we can get FHitung 0,003 is smaller from FTabel 10,127. It explains that H0 is accepted to reject H1. Therefore, it can conclude that there is not significant influence to use variation of concentration of activator HCl to adsorption capacity of charcoal active from cocoa’s peel in substance methanil yellow.